The 7-α-dehydroxylation pathway: An integral component of gut bacterial bile acid metabolism and potential therapeutic target - Wise, Journey L.; Cummings, Bethany P. (Frontiers in Microbiology, 2023)
The gut microbiome plays a significant role in maintaining host metabolic health through the production of metabolites. Comprising one of the most abundant and diverse forms of gut metabolites, bile acids play a key role in blood glucose regulation, insulin sensitivity, obesity, and energy expenditure. A central pathway in gut bacterial bile acid metabolism is the production of secondary bile acids via 7-ɑ-dehydroxylation. Despite the important role of 7-ɑ-dehydroxylation in gut bacterial bile acid metabolism and the pathophysiology of metabolic disease, the regulation of this pathway is not completely understood. This review aims to outline our current understanding of 7-ɑ-dehydroxylation and to identify key knowledge gaps that will be integral in further characterizing gut bacterial bile acid metabolism as a potential therapeutic target for treating metabolic dysregulation.